Preponderance of Bioactive Medicinal Compounds and ATR-FTIR Spectroscopy of Coriander and Mustard Floral Honey from Apis mellifera - Ishan Ullah Khan; Widhi Dubey; Vedprakash Gupta (Indonesian Journal of Chemistry, 2017)
The physicochemical, total phenolics, flavonoids, and antioxidant activity were evaluated for biochemical characterization of coriander and mustard floral honey. The total phenolics, flavonoids and antioxidant activity were analyzed using UV-VIS spectrophotometer. Fourier transform infrared spectroscopy (FT-IR) was used to evaluate the chemical characteristic of coriander and mustard floral honey. The total phenolics content was ranged from 294 to 462 mg gallic acid equivalent kg-1 of honey. The total flavonoid content was ranged from 43 to 53 mg quercetin equivalent kg-1 of honey. Antioxidant activity results were expressed as inhibitory concentration (IC50) value ranged from 4.58 to 5.54 mg mL-1. FT-IR spectra showed the presence of alcohols, carboxylic acids, esters, ethers, phenols, and amines in both floral honey samples. This study discovered that coriander floral honey is more affluent than mustard floral honey in nutritional as well as medicinal aspects. At a glance the processing of honey by heating did not affect the phenolics, flavonoid, and antioxidants of honey; even processed honey contains higher phenols and antioxidants. The FT-IR spectra showed the similarity in both kinds of honey refers to chemical constituents. This study will help the researcher and honey consumer to find out the higher bioactive medicinal compounds containing honey.